2018
DOI: 10.1093/ajh/hpy143
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitor, Febuxostat Ameliorates the High Salt Intake–Induced Cardiac Hypertrophy and Fibrosis in Dahl Salt-Sensitive Rats

Abstract: BACKGROUND Xanthine oxidase (XO) is a source of reactive oxygen species production in the heart. However, pathophysiological role of XO has not been clarified in hypertensive heart disease. Thus, the present study examined the impacts of high salt (HS) intake and febuxostat (Fx), a XO inhibitor in Dahl salt-sensitive (Dahl-S) rats. METHODS Eight-week old, male Dahl-S rats were fed a normal salt diet (0.6% NaCl) or a HS diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Fructose and condensed milk were selected since both of them are commonly found in the western style diet. Regarding the effects of salt on blood pressure, several studies showed that a diet containing 4–8% of NaCl successfully induced hypertension in rats, while a diet containing 0.25–0.6% of NaCl was used as a control diet and did not affect the blood pressure . Therefore, 0.1% NaCl in our diet, which was lower than the amount of sodium in the control diet in that report, could not affect blood pressure in our animal model.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Fructose and condensed milk were selected since both of them are commonly found in the western style diet. Regarding the effects of salt on blood pressure, several studies showed that a diet containing 4–8% of NaCl successfully induced hypertension in rats, while a diet containing 0.25–0.6% of NaCl was used as a control diet and did not affect the blood pressure . Therefore, 0.1% NaCl in our diet, which was lower than the amount of sodium in the control diet in that report, could not affect blood pressure in our animal model.…”
Section: Discussionmentioning
confidence: 65%
“…Regarding the effects of salt on blood pressure, several studies showed that a diet containing 4-8% of NaCl successfully induced hypertension in rats, while a diet containing 0.25-0.6% of NaCl was used as a control diet and did not affect the blood pressure. [20][21][22] Therefore, 0.1% NaCl in our diet, which was lower than the amount of sodium in the control diet in that report, could not affect blood pressure in our animal model. From our blood pressure data, both systolic and diastolic blood pressure were similarly increased after 16 weeks of HFD or HFHS consumption.…”
Section: Discussionmentioning
confidence: 91%
“…UA also can cause mitochondrial alterations and decrease intracellular ATP production and subsequently result in endothelial dysfunction in human aortic endothelial cells 41. A large quantity of animal experiments and human epidemiological documents indicated that SUA-lowering treatment was beneficial for CVDs 43–47…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In Dahl salt-sensitive rats fed a high salt diet with subsequent development of hypertension, LV hypertrophy, and cardiac fibrosis an XO inhibitor blocked the increase in XO activity and attenuated LV hypertrophy and fibrosis independent of changes in blood pressure. 27 With regard to our 91 RHTN patients, neither ACE inhibitor nor AT 1 receptor blocker alone or in combination affected plasma XO activity. Taken together, the failure of spironolactone therapy to reduce XO activity in the face of an unrestricted salt diet further suggests the effect of salt alone on the induction of oxidative stress in RHTN.…”
Section: Discussionmentioning
confidence: 71%
“…26 Pertinent to the current study, high salt intake was demonstrated to increase XO activity in the hypertrophied left ventricle of a Dahl salt-sensitive model of hypertension. 27 Sowers et al have also shown that mice fed a Western diet have increased production of uric acid with increased LV XO activity, inflammation, fibrosis, and impaired diastolic relaxation; all results improved with allopurinol treatment. 28 Taken together, these findings, coupled with the well-documented link of a high salt diet and oxidative stress, led us to conduct the current retrospective analysis in which we hypothesize that increased plasma XO activity is related to 24-hour urinary sodium and to LV hypertrophy and diastolic dysfunction in a large cohort of RHTN patients.…”
Section: Introductionmentioning
confidence: 96%